(untitled) (AYUSHDHARA, 2018)
Life style modulated diseases have overpowered the human over a decade. Sedentary life, Virudhaaahar, over sweating. Due to this life style factors reduction in skin based immunity takes place which leads to Kustharoga. Dadru which comes under Kshudraroga. Dadru has classical symptoms mainly of itching (Kandu), reddish patches with prominent edges (Mugdagatam, Mandalaakruti). Materials & Method: Nimba has Tikta rasa katuvipak and Shitavirya. It leaves have properties like Krumighna, Vranashodhan, Putihar, Dahaprashaman and Kandughna. It is included under Kandughnagana. Patrapottaliswedan is consider under Sankarsweda told by Acharya charaka. Hence Nimbapatrapottali swedan has significant result in Dadru. There is a significant relief in itching (Kandu), redness and the prominent edges of the patches are reduced. To prove the efficacy of Nimbapatrapottali swedan in Dadruroga 4 patients were selected with classical symptoms of Dadru from Panchakarma OPD and IPD of Y.M.T. medical college. Result: A course of Nimba patrapottali swedan for 11 days and orally Nimbachala Ghana vati for 3 month was done on the subjective parameter. Significant changes were observed in subjective parameter.